Pengaruh Social Support terhadap Academic Burnout pada Mahasiswa Program Studi Sarjana Kedokteran di Kota Bandung - Salsa Alfi Syahrin; Kusdiyati, Sulisworo (UNISBA Press, 2024)
Abstract. Medical students in West Java are said to have the highest level of Academic Burnout compared to other medical students in Indonesia. Academic Burnout is the impact of large academic demands and challenges, especially on medical students. In this research, Social Support is the independent variable and Academic Burnout is the dependent variable, considering that Social Support is said to be a variable that produces various results regarding its influence and relationship to Academic Burnout. The aim of this research is to try to determine the level of Social Support and Academic Burnout as well as the influence of Social Support on Academic Burnout in students of the Undergraduate Medical Study Program in Bandung City. The design of this research is causality with a non-experimental quantitative approach. Data were collected using a cross-sectional convenience sampling technique with 311 medical students as respondents. Multiple regression analysis was used to see the influence of the Social Support dimension on Academic Burnout. The theory used to explain Social Support is Cohen & Hoberman's Theory (1983) and to explain Academic Burnout using the Theory of Schaufeli et al., (2002). The research results based on the R Square value of Social Support contribute 67% to the Academic Burnout variable with a significant negative relationship, meaning that the higher the level of appreciation of Social Support, the lower the level of Academic Burnout and vice versa. Of the 4 dimensions of Social Support (appraisal support, belonging support, tangible support, and esteem support) Belonging Support is the dimension that has the most influence on Academic Burnout with a contribution value (R2) of 26.3%. Abstrak. Mahasiswa kedokteran di Jawa Barat dikatakan berada pada tingkat tertinggi mengenai Academic Burnout dibandingkan dengan mahasiswa kedokteran lainnya di Indonesia. Academic Burnout adalah dampak dari besarnya tuntutan dan tantangan akademik terutama pada mahasiswa Kedokteran. Pada penelitian ini Social Support sebagai variabel independent dan Academic Burnout sebagai variabel dependen, mengingat Social Support dikatakan sebagai variabel yang memunculkan hasil yang beragam mengenai pengaruh dan hubungannya terhadap Academic Burnout. Tujuan penelitian ini mencoba mengetahui tingkat Social Support dan Academic Burnout serta pengaruh Social Support terhadap Academic Burnout pada mahasiswa Program Studi Sarjana Kedokteran di Kota Bandung. Desain penelitian ini adalah kausalitas dengan pendekatan kuantitatif non ekperimental. Pengambilan data menggunakan teknik convevience sampling secara cross-sectional pada responden sebanyak 311 mahasiswa kedokteran. Analisis regresi berganda digunakan untuk melihat pengaruh dari dimensi Social Support terhadap Academic Burnout. Teori yang digunakan untuk menjelaskan Social Support adalah Teori Cohen & Hoberman (1983) dan untuk menjelaskan Academic Burnout menggunakan Teori Schaufeli et al., (2002). Hasil penelitian berdasarkan nilai R Square Social Support berkontribusi sebesar 67% terhadap variabel Academic Burnout dengan arah hubungan negatif yang signifikan artinya semakin tinggi tingkat penghayatan Social Support maka akan semakin rendah tingkat Academic Burnoutnya begitupun sebaliknya. Adapun dari 4 dimensi Social Support (appraisal support, belonging support, tangible support, dan esteem support) Belonging Support merupakan dimensi yang paling berpengaruh terhadap Academic Burnout dengan nilai kontribusi (R2) sebesar 26,3%.